Integration of evidence to evaluate the potential for neurobehavioral effects following exposure to USFDA-approved food colors. (May 2021) - Gentry, Robinan; Greene, Tracy; Chappell, Grace; Lea, Isabel; Borghoff, Susan; Yang, Chihae; Rathman, James; Ribeiro, João Vinnie; Hobocienski, Bryan; Mostrag, Aleksandra; Rodricks, Joseph; Clewell, Harvey
Abstract: California's Office of Environmental Health Hazard Assessment was tasked with conducting risk assessments for United States Food and Drug Administration-approved food dyes relative to neurobehavioral concerns. The purpose of this assessment was to evaluate the evidence for neurodevelopment effects based on three streams of evidence: 1) studies identified by OEHHA for consideration in a quantitative risk assessment; 2) studies relevant to understanding mechanisms of neurobehavioral effects; 3) an in silico assessment of the bioavailability of USFDA-approved food dyes. The results indicate a lack of adequate or consistent evidence of neurological effects, supported by a lack of bioavailability and brain penetration predicted by the in silico assessment. Further, the mechanistic evidence supports a lack of activity from in vitro neurotransmitter assays, and a lack of evidence to support molecular initiating events or key events in adverse outcome pathways associated with neurodevelopmental effects, supporting a lack of biological plausibility for neurobehavioral effects following food exposures to colors. These conclusions are consistent with other authoritative bodies, such as JECFA and EFSA, that have determined (i) other effects are more appropriate for estimating acceptable daily intakes and (ii) evidence from the neurobehavioral studies lack the strength to be relied upon for quantitative risk assessment. Highlights: OEHHA tasked with conducting neurological risk assessments for synthetic colors. Current assessment conducted for evidence of neurological effects for synthetic colors. Integration of evidence provided no adequate or consistent evidence of effects. Lack of bioavailability/brain penetration demonstrated based on in silico results. Results are consistent with conclusions from authoritative bodies (JECFA, EFSA).